Sport-related concussions in wrestling: does mechanism of injury affect recovery? - Dugan, J. E.; Jo, J.; Williams, K. L.; Terry, D. P.; Zuckerman, S. L. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Sport-related concussions (SRC) represent a significant concern for athletes. While popular contact sports such as football and soccer have been the focus of much SRC research, wrestling has received comparatively little attention. The current study aimed to: 1) describe the mechanisms of injury leading to SRC in wrestling; and 2) compare recovery outcomes based on mechanism of injury. METHODS: A retrospective, cohort study of wrestlers aged 12-18 who sustained a concussion between 11/2017-04/2022 was performed. Contact mechanism was defined as what initiated contact with the athlete`s head/body. Player mechanism was defined as the activity the injured athlete was performing when the concussion occurred. Recovery outcomes were compared using Mann-Whitney-U Tests and multivariable regression analysis. RESULTS: Seventy-three (age=15.8±1.4 years; boys=73 [100.0%]) wrestlers were included. SRCs occurred more often in competition than in practice (66.2% vs. 33.8%, respectively). Head-to-ground/wall (56.2%) and takedown (58.9%) were the most common contact and player mechanisms, respectively. Bivariate analysis showed that head-to-head/body SRCs had longer time to symptom resolution compared to head-to-ground/wall SRCs (23.0 [14.8-46.5] vs. 14.0 [6.0-30.0] days; U=149.00, P=0.029), though the difference did not persist in multivariable analysis. For player mechanism, non-takedowns SRCs had longer time to symptom resolution than takedown SRCs (15.0 [6.0-24.0] vs. 28.5 [13.0-49.3]; U=166.5, P=0.019), but the difference also did not persist in multivariable analysis. Bivariate analysis revealed no significant difference in RTL between takedown and non-takedown SRCs (3.0 [2.0-6.0] vs. 4.0 [1.5-7.0]; U=484.50, P=0.708); however, in multivariable analysis, takedown SRCs were associated with longer RTL (ß=0.23, 95% CI: 0.02, 9.27; P=0.049). CONCLUSIONS: The current study found that SRCs occurred more commonly during competitions, and head-to-ground/wall and takedown were the most common contact and player mechanism, respectively. SRCs that occurred during takedowns were associated with longer RTL.